Design of SMB chiral separations using the concept of separation volume - Rodrigues, Alírio (2009)
The article deals with chiral separation by simulated moving bed (SMB) chromatography. When mass transfer resistances are negligible, equilibrium theory provides explicit criteria for the choice of the SMB operating conditions. However, in the presence of mass transfer resistances, the SMB operating conditions should be evaluated through simulation. Using a package based on the analogy with the true moving bed operation, this work shows how mass transfer resistance can affect the conditions for enantiomers separation, as well as the critical values stated by equilibrium theory. The concept of separation volume is applied to show how the flow-rate constraints, in presence of mass transfer resistances, have to be modified for chiral separations in which the adsorption equilibrium isotherms of both enantiomers are of linear + Langmuir type.